Pastures anti-A therapy. Product (1ra part) advance - Gálvez Calla, Luis H. (2005)
«in vitro & in vivo» studies of fue Anti-A Experimental Paste, with the help of Sangre de grado and tricalcic phosphate, they have shown an excellent capacity germicide and reparative of the conjunctive tissue. The fibroblástic activity observed in most of the cases, probably generated by effects of the tricálcic phosphate, is the same one that showed a similar behavior in a previous investigation, inducing the reparative process of the bony defects. However, the application of the Anti-A Experimental Paste in human in posexodoncic ad that showed dilution with the saliva and lack of adhesion tissue, believe the necessity to continue with the investigation line with the purpose of improving their original properties, incorporating biocompatible additives. the study consisted on elaborating 8 pastes with diverse formulations with the help of Sangre de grado, tricálcic phosphate, rubber tragacanto, propilenglycol, vaseline, metil parabeno and it dilutes distilled; not evaluated with laboratory tests in order to readjust and to gauge the proporcionalidades of the inputs in funtion to the properties preservantes, adhesive, absorbent and of antibacterian action; what allowed to discard some formulations and to continue with those that contain reduced quantities in grams rubber tragacanto and vaseline in the formulation The results showed an appropriale diffusion of the active principle and a good antibacterian activity in front of the grampositives and gramnegatives. The biodegradable and reparative property will be evaluated in later investigations before its application in human.